From Sugar to Splenda A Personal and Scientific Journey of a Carbohydrate Chemist and Expert Witness - Fraser-Reid, Bert.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
More than just coincidence connects a Tate & Lyle lawsuit and artificial sweetener to Jamaican-born Chemist Bert Fraser-Reid. From his first experience of Chemistry through his diabetic father, to his determination and drive as a Chemistry student in Canada, Fraser-Reid weaves a remarkable tale integrating science, law and autobiographical anecdotes. This book arises from the lawsuit brought by Tate & Lyle against companies accused of infringing its patents for sucralose, the sweet ingredient in the artificial sweetener SPLENDA which is made by chlorinating sugar. From a 1958 undergraduate intern witnessing the pioneering experiments on sugar chlorination, to being the 1991 recipient of the world$1 (Bs premiere prize for carbohydrate chemistry, Fraser-Reid was groomed for his role as expert witness in the mentioned lawsuit. Nevertheless, it seems more than his career links Fraser-Reid to the case.s
Jamaica -- The Author in Jamaica -- Canada - very fortunately -- London - Hough, Khan and Pfadnis get together -- Sweetness -- "Luck" -- Prepping for the Trial - Identifying "Swords of Damocles" -- Preamble to the Trial -- Day One of the Trial -- Day Two of the Trial -- Day Three of the Trial -- Day Four of the Trial -- Day Five of the Trial -- Day Six of the Trial -- Days Seven and Eight of the Trial: My time on the Witness Stand -- Appendices.
Keywords: Chemistry; Food science; Carbohydrates; Diabetes; Mathematics; Commercial law; Chemistry; Carbohydrate Chemistry; Commercial Law; Food Science; Popular Science in Mathematics/Computer Science/Natural Science/Technology.; Diabetes